Thromboelastography demonstrates progressive hypercoagulability in COVID-19 patients admitted to ICU with respiratory failure. (November 2022) - Joshi, Kunal; Fabes, Jeremy; Melikian, Clare; Spiro, Michael
Thromboembolic complications are associated with COVID-19 owing to the hypercoagulable nature of the disease. Although patients with COVID-19 often have higher levels of fibrinogen and D-dimers, hypercoagulability has been attributed to various other factors too. In this prospective observational study conducted between April 2020 and June 2020, we compared coagulation parameters using thromboelastography in COVID-19 patients to non-COVID-19 patients admitted to ICU with respiratory failure. This study demonstrated a significant difference between the cohorts in functional fibrinogen (CFF) progressively from third day of ICU admission whilst there was no difference in the Clauss fibrinogen levels. COVID-19 patients also demonstarted supranormal R time indicating hypocoagulability. These mixed coagulation changes suggest targeting fibrinogen or platelets may prevent thromboembolic complications in COVID-19.